The Productivity of Pre-Merger State-Owned Islamic Banks in Indonesia - Atika Ayuning Tyas; Aam Slamet Rusydiana (Ekonomi Islam Indonesia, 2020)
Recently, the Ministry of State-Owned Enterprises (BUMN) has decided to merge Bank BRI Syariah (BRIS), Bank Syariah Mandiri (BSM), and Bank BNI Syariah to improve the development of the Islamic economy in Indonesia. This merger plan is implemented to increase the share of the Islamic banking market so that it can compete with conventional banking. To be able to compete with conventional banking, Islamic banks must be able to have high productivity performance. Therefore, this study will analyze and compare the productivity of the performance of BRIS, BSM, and BNIS with the productivity of the performance of 10 conventional banks for the period 2016-2019. The method used is the Malmquist Productivity Index (MPI) with 5 analysis models to obtain various considerations in preparing the merger plan. The estimation results show that if the three banks are merged, they will have a performance productivity level of 1.196. On the other hand, if only two Islamic banks are merged, the merger that will result in a high productivity level of performance will only occur in the merger of BNIS and BRIS with a productivity level of 1.097